2015
DOI: 10.3109/07853890.2015.1073346
|View full text |Cite
|
Sign up to set email alerts
|

Stanford-A acute aortic dissection, inflammation, and metalloproteinases: A review

Abstract: Acute aortic dissection (AAD) is a life-threatening disease with an incidence of about 2.6-3.6 cases per 100,000/year. Depending on the site of rupture, AAD is classified as Stanford-A when the ascending aortic thoracic tract and/or the arch are involved, and Stanford-B when the descending thoracic aorta and/or aortic abdominal tract are targeted. It was recently shown that inflammatory pathways underlie aortic rupture in both type A and type B Stanford AAD. An immune infiltrate has been found within the middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
119
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 70 publications
0
119
0
Order By: Relevance
“…Furthermore, increased neutrophils, macrophages, and MMP-9 have been detected in aortic tissue or blood of patients with AD (14-17). MMP-9, which degrades elastin and collagens, can be produced by neutrophils, macrophages, or vascular smooth muscle cells (16,18). Our studies using adoptive transfer of WT or LNK-deficient leukocytes into Rag1 -/mice demonstrate that loss of LNK in immune cells plays a key role in development of AD ( Figure 4) and that Lnk -/neutrophils secrete more MMP-9 when activated ex vivo and exhibit increased migratory capacity in the setting of Ang II infusion ( Figure 5, D and E).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased neutrophils, macrophages, and MMP-9 have been detected in aortic tissue or blood of patients with AD (14-17). MMP-9, which degrades elastin and collagens, can be produced by neutrophils, macrophages, or vascular smooth muscle cells (16,18). Our studies using adoptive transfer of WT or LNK-deficient leukocytes into Rag1 -/mice demonstrate that loss of LNK in immune cells plays a key role in development of AD ( Figure 4) and that Lnk -/neutrophils secrete more MMP-9 when activated ex vivo and exhibit increased migratory capacity in the setting of Ang II infusion ( Figure 5, D and E).…”
Section: Discussionmentioning
confidence: 99%
“…1) It is classified as Stanford type A when the ascending aortic thoracic tract is involved and Stanford type B when the descending thoracic aorta is targeted. 2,3) As the most common thoracic aortic emergency, AAD may be rapidly fatal without early diagnosis and appropriate management, 4) and it may be associated with giant cell arteritis.…”
mentioning
confidence: 99%
“…Studies in human AD samples and animal AD models indicate that inflammatory response plays a central role in the pathogenesis of AD [3,4]. We also reported the involvement of inflammatory response in mouse models [5][6][7] and in human AD tissue [8].…”
Section: Introductionmentioning
confidence: 58%
“…As the transcriptome analysis suggested that MRTF-A regulates the inflammatory response that plays a central role in AD pathogenesis [3,4], we performed quantitative analysis of inflammatory cytokines by qRT-PCR in aortic tissue (Fig 4). The mRNA expressions of Il6 and Ccl2 were induced by 1 day of AngII infusion in WT aorta, while this response was not observed in MRTF-A-KO mice (Fig 4A).…”
Section: Role Of Mrtf-a In Aortic Wall Inflammation and Apoptosismentioning
confidence: 99%